Kerja Sama Luar Negeri oleh Pemerintah Daerah (Sister City) antara Kota Medan dengan Kota Gwangju - Damanik, Anne F.; Ridho, Hatta; Nasution, Indra Kesuma (Universitas Medan Area, 2024)
This study aims to understand how the sister city partnership between Medan and Gwangju is implemented in the development of Medan and to identify the factors influencing the execution of this partnership which, over 26 years, has not significantly impacted Medan's development. The approach used is based on Discursive Institutional theory. This research employs a qualitative methodology that addresses and resolves research problems using normative and empirical approaches. The data analysis techniques include data reduction, data presentation, and conclusion drawing. The findings indicate that institutional functions within the international city-to-city cooperation, specifically between Medan and Gwangju, have not been effectively executed by the institutions acting as partners in the sister city cooperation. These functions include: (1) Coordinative Function, consisting of factors such as Commitment to Link, Leadership, Structure and Management, Communication, and Monitoring and Evaluation; (2) Communicative Function.